1999
DOI: 10.1557/proc-566-197
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Dependent Modeling for CMP Optimization and Control

Abstract: In previous work, we have formalized the notions of "planarization length" and "planarization response function" as key parameters that characterize a given CMP consumable set and process. Once extracted through experiments using carefully designed characterization mask sets, these parameters can be used to predict polish performance in CMP for arbitrary product layouts. The methodology has proven effective at predicting oxide interlevel dielectric planarization results.In this work, we discuss extensions of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…It was already shown that a combination of line width, pattern density, pad rigidity and the applied down pressure determine not only the material removal rate but also the amount of dishing and erosion. 5,6,[8][9][10][11] Also, for CMP of Cu lines with an oxide spacer, Lin et al5 modeled the effect of line width, pattern density, pad rigidity and applied down pressure on dishing and showed that the line width and the applied down pressure, but not pad rigidity or pattern density, have a more significant effect on dishing, and confirmed it experimentally. Indeed, it was also shown that the optimization of pressure settings during the polishing process can contribute to lower dishing.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…It was already shown that a combination of line width, pattern density, pad rigidity and the applied down pressure determine not only the material removal rate but also the amount of dishing and erosion. 5,6,[8][9][10][11] Also, for CMP of Cu lines with an oxide spacer, Lin et al5 modeled the effect of line width, pattern density, pad rigidity and applied down pressure on dishing and showed that the line width and the applied down pressure, but not pad rigidity or pattern density, have a more significant effect on dishing, and confirmed it experimentally. Indeed, it was also shown that the optimization of pressure settings during the polishing process can contribute to lower dishing.…”
mentioning
confidence: 94%
“…It was already shown that a combination of line width, pattern density, pad rigidity and the applied down pressure determine not only the material removal rate but also the amount of dishing and erosion. 5,6,[8][9][10][11] Also, for CMP of Cu lines with an oxide spacer, Lin et al…”
mentioning
confidence: 99%
“…There are several CMP models [4][5][6][7][8]. These models, however, have been mainly concerned with the mechanical aspects of the process.…”
Section: Introductionmentioning
confidence: 99%
“…The CD drop at the boundary region becomes severe with increasing etching target because etching amount does not increase equally due to different pattern density. This phenomenon can be observed in CMP process as well [4]. Even though this kind of CD variation is quite small, about 0.2nm corresponding to 6nm AEI CD increase, it would not be negligible if several etch and CMP step is repeated amplifying CD drop at boundary region.…”
Section: Other Process Issues: Etch and Cmp Loading Effectmentioning
confidence: 84%